The Strategy of Mosques as a Medium for Economic Empowerment of the Muslim Community in Watampone City - Rosmini Rosmini; Arifin Sahaka; Ahmad Abdul Mutalib (International Forum of Researchers and Lecturers, 2025)
This study examines and analyzes the strategies of mosques as a medium for empowering the community's economy in the city of Watampone. The main focus of the research is to identify the types of strategies implemented by mosques, the challenges faced in carrying out economic programs, and to formulate effective strategies for improving community welfare based on mosque-centered initiatives.The research method used is qualitative descriptive, with data collected through interviews, observations, and documentation of four main mosques in Watampone City: Masjid Agung al-Malkaz al-Ma’arif, Masjid Nurul Hamirah, Masjid Tua Al-Mujahidin, and Masjid Songko’ Recca. The findings reveal that mosques in Watampone have implemented two strategic approaches to economic empowerment: offline (physical) and online (digital). (1) Offline strategies are carried out through the utilization of physical assets such as hall rentals, the establishment of business units, and the organization of social and educational activities.(2) Online strategies are still limited to the use of QRIS for donations and da'wah media, and have not yet extended to digital economic empowerment such as sharia-based marketplaces or online training platforms. In practice, mosques utilize several Islamic economic contracts, including ijarah, muḍarabah, and wakalah. The implementation of these empowerment programs faces several internal and external challenges. This study formulates six effective strategies to address these challenges. These findings are expected to serve as strategic recommendations for mosque administrators, government institutions, and the broader community in enhancing the role of mosques as centers of community economic empowerment.